Employing participatory methods to engage an under-researched group: Opportunities and challenges. Issue 1 (April 2018) - Pettinger, Clare; Letherby, Gayle; Parsons, Julie M; Withers, Lyndsey; Cunningham, Miranda; Whiteford, Andrew; D'Aprano, Gia; Ayres, Richard; Sutton, Carole
In this article, we report on our experience of working on an exploratory project where the primary objective was to involve homeless service users with food-based participatory qualitative approaches. The project FLM aimed to explore food experiences and behaviours in a sample of users of homelessness services in a south west UK coastal city, in order to create solutions to improve their wellbeing. A mixture of qualitative methods was used, including observations, photo-elicitation and focus group discussions. We aimed to be participatory and 'creative' in our approach and in our analysis. Here, we focus on detailing and critiquing our approach to the collection and analysis of data.